Ethics and conflict of interest in psychiatric research - Fernando Portela Câmara (Revista Latinoamericana de Psicopatologia Fundamental, 2006)
This article discusses the relationship between personal interests and medical research. The presence of research professionals who conduct studies which will laterbe used for market investments through new pharmaceutical products or procedures has brought up a number of issues, especially regarding the neutrality of the use of such products. The fact that some researchers receive shares in stocks and profits of some companies, and the way the companies finance them and use their credibility in scientific marketing have been a source of concern to scientific journals, the academic community and the better-informed public as to the validity of the results presented and the reliability of the pharmaceutical products themselves. The question of how neutrality can be preserved without the inevitable involvement of these interests is an ethical issue that has yet to be carefully examined by agencies that regulate the medical profession.